Mastery, perceived stress and health-related behaviour in northeast Arnhem Land: a cross-sectional study - Brown Alex; Daniel Mark; Dhurrkay J Garnggulkpuy; Cargo Margaret D; O'Dea Kerin (BMC, 2006)
Abstract Background Indigenous peoples in Australia are disadvantaged on all markers of health and social status across the life course. Psychosocial factors are implicated in the aetiology of chronic diseases and in pathways underpinning social health disparities. Minimal research has investigated psychosocial factors and health in Indigenous peoples. This study evaluated associations between mastery, perceived stress, and health-related behaviour for a remote Indigenous population in Australia. Methods Complete data on mastery (the degree to which individuals feel in control of their lives), perceived stress, physical activity, and fruit and vegetable consumption were obtained for 177 participants in a community-based chronic disease risk factor survey. Psychosocial questionnaires were completed as an option during community screening (response rate = 61.9%). Extensive consultation facilitated the cross-cultural adaptation of measures. Results Mastery was inversely correlated with perceived stress measures (p < 0.009): recent stress, r = -0.47; chronic stress, r = -0.41; and youth stress, r = -0.30. Relationships between mastery and behaviour varied according to age group (<25 or ≥25 years) for physical activity (p = 0.001) and vegetable consumption (p = 0.005). Individuals aged ≥25 years engaging in ≤2 bouts of physical activity/week had lower mastery than individuals engaging in ≥3 bouts/week, with means (95% CI) of 14.8 (13.7-15.8) and 17.1 (15.3-19.0), respectively (p = 0.026). Individuals aged ≥25 years eating vegetables ≤3 times/week had lower mastery than those eating vegetables ≥4 times/week (p = 0.009) [means 14.7 (13.8-15.5) and 17.3 (15.5-19.1), respectively]. Individuals <25 years engaging in ≤2 bouts of physical activity/week had greater mastery than individuals engaging in ≥3 bouts/week (p = 0.022) [means 17.2 (15.2-19.2) and 13.8 (11.9-15.7), respectively]. For men ≥25 years and women ≥15 years, mastery was inversely related to age (p < 0.002). Men <25 years had less mastery than women of equivalent age (p = 0.001) [means 13.4 (12.1-14.7) and 17.5 (15.3-19.8), respectively]. Conclusion Consistent with previous research, this study provides additional support for a link between mastery and health-related behaviour, and extends evidence of this association to a remote Indigenous population. Mastery's association with perceived stress, its age-specific association with health behaviour, and findings of low mastery amongst young men, highlights a need for life course research accounting for contextual factors affecting Indigenous peoples.